Content Characteristics of GRE Analytical Reasoning Items. GRE Board Professional Report No. 84-14P - Chalifour, Clark; Powers, Donald E.; Educational Testing Service, Princeton, NJ. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
In actual test development practice, the number of test items that must be developed and pretested is typically greater, and sometimes much greater, than the number eventually judged suitable for use in operational test forms. This has proven to be especially true for analytical reasoning items, which currently form the bulk of the analytical ability measure of the Graduate Record Examination (GRE) General Test. This study involved coding the content characteristics of some 1,400 GRE analytical reasoning items and correlating them with indices of item difficulty, discrimination, and independence from the verbal and quantitative measures. Several item characteristics were predictive of the difficulty of analytical reasoning items. Generally, these same variables predicted item discrimination, but to a lesser degree. Independence from the GRE verbal and quantitative measures was largely unpredictable. The results suggest several content characteristics that could be considered in extending the current specifications for analytical reasoning items. The use of these item features may also contribute to greater efficiency in developing such items. Appendix A gives examples of analytical reasoning sets, and appendix B contains variable definitions and instructions to raters. (Contains 5 tables and 23 references.) (Author/SLD)
Sponsoring Agency: Graduate Record Examinations Board, Princeton, NJ.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Coding; Difficulty Level; Higher Education; Test Construction; Test Content; Test Items; Analytical Reasoning -- Graduate Record Examinations; Test Specifications; Reports, Evaluative